Relative bradycardia as a clinical feature in patients with coronavirus disease 2019 (COVID-19): A report of two cases. Issue 6 (December 2020) - Hiraiwa, Hiroaki; Goto, Yukari; Nakamura, Genki; Yasuda, Yuma; Sakai, Yoshinori; Kasugai, Daisuke; Jinno, Shinsuke; Tanaka, Taku; Ogawa, Hiroaki; Higashi, Michiko; Yamamoto, Takanori; Jingushi, Naruhiro; et al.
Abstract: We treated two patients with COVID-19 pneumonia requiring mechanical ventilation. Case 1 was a 73-year-old Japanese man. Computed tomography (CT) revealed ground-glass opacities in both lungs. He had severe respiratory failure with a partial pressure of oxygen in arterial blood/fraction of inspiratory oxygen ratio (P/F ratio) of 203. Electrocardiogram showed a heart rate (HR) of 56 beats/min, slight ST depression in leads II, III, and aVF, and mild saddle-back type ST elevation in leads V1 and V2. High-sensitivity cardiac troponin T (cTnT) level was slightly elevated. Despite a high fever and hypoxemia, his HR remained within 50–70 beats/min. Case 2 was a 52-year-old Japanese woman. CT revealed ground-glass opacities in the lower left lung. Electrocardiogram showed a HR of only 81 beats/min, despite a body temperature of 39.2 °C, slight ST depression in leads V4, V5, V6, and a prominent U wave in multiple leads. She had an elevated cTnT and a P/F ratio of 165. Despite a high fever and hypoxemia, her HR remained within 50–70 beats/min. Both patients had a poor compensatory increase in their HR, despite their critical status. Relative bradycardia could be a cardiovascular complication and is an important clinical finding in patients with COVID-19. <Learning objective: We report two Japanese cases of COVID-19 pneumonia with relative bradycardia as a condition and no significant compensatory increase in heart rate despite high fever and severe hypoxemia. Relative bradycardia in COVID-19 might be associated with myocardial injury due to not only direct viral involvement but also systemic inflammation. We should carefully observe the occurrence of relative bradycardia because it could potentially be a clinical sign of COVID-19.>